Efficiency of Air Purifiers at Removing Air Pollutants in Educational Facilities: A Preliminary Study - Brągoszewska, Ewa; Biedroń, Izabela (Frontiers in Environmental Science, 2021)
Infectious diseases caused by airborne bacteria and viruses are a major problem for both social and economic reasons. The significance of this phenomenon is particularly noticeable during the time of the coronavirus pandemic. One of the consequences is the increased interest in the air purifier (AP) market, which resulted in a significant increase in sales of these devices. In this study, we tested the efficiency of APs in removing bacterial air contamination in the educational context in the Upper Silesia region of Poland during the ‘cold season’ of 2018/2019. During the six months of measuring microbiological air quality, an 18% decrease in the concentration of microbiological pollutants as a result of the action of the APs was recorded. Additionally, the results of the particle size distribution of the bacterial aerosols showed a reduction in the share of the respirable fraction (particles with an aerodynamic diameter below 3.3 µm) by an average of 20%. The dominance of Gram-positive cocci in the indoor environment indicates that humans are the main source of most of the bacteria present in the building. We conclude that the use of APs may significantly decrease the level of concentration of microbiological air pollutants and reduce the negative health effects of indoor bioaerosols; however, further work that documents this phenomenon is needed.